2009
DOI: 10.1002/dev.20364
|View full text |Cite
|
Sign up to set email alerts
|

Early lead exposure effects on an auditory threshold task in the rhesus monkey (Macaca mulatta)

Abstract: Behavioral thresholds to pure tones were obtained from adult rhesus monkeys that had been exposed to lead during early development and unexposed cohort controls. Thresholds were elevated (by 2-9 dB) for the previously lead exposed monkeys at all frequencies tested (125-8,000 Hz in octave steps). Although the magnitude and direction of the differences were similar to significant effects reported for children, the more difficult task and much smaller sample sizes in this study of monkeys may have precluded obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In follow-up investigations, using DPOAE and other physiologic auditory measures with monkeys, no evidence was found for Pb effects on middle ear, auditory sensory or auditory neural functioning (Lasky et al, 2001a, 2001b). In a recent investigation by Laughlin, et al (2009), mean behavioral pure-tone thresholds for 5 monkeys ( Macaca mulatta ) exposed to Pb during early development were observed to be elevated compared to 5 control monkeys for frequencies from 125–8000 Hz, but this difference was statistically significant only at 250 Hz. As previously indicated, if one assumes that Pb is an ototoxin, significant effects would be expected at the higher frequencies more so than lower frequencies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In follow-up investigations, using DPOAE and other physiologic auditory measures with monkeys, no evidence was found for Pb effects on middle ear, auditory sensory or auditory neural functioning (Lasky et al, 2001a, 2001b). In a recent investigation by Laughlin, et al (2009), mean behavioral pure-tone thresholds for 5 monkeys ( Macaca mulatta ) exposed to Pb during early development were observed to be elevated compared to 5 control monkeys for frequencies from 125–8000 Hz, but this difference was statistically significant only at 250 Hz. As previously indicated, if one assumes that Pb is an ototoxin, significant effects would be expected at the higher frequencies more so than lower frequencies.…”
Section: Discussionmentioning
confidence: 91%
“…As previously indicated, if one assumes that Pb is an ototoxin, significant effects would be expected at the higher frequencies more so than lower frequencies. It is difficult to draw any firm conclusions from the Laughlin, et al (2009) study because of the small sample size, and because the Pb-exposed monkeys were reported to be more difficult to test and less engaged in the auditory threshold task than controls. The less than optimal task performance behaviors by the Pb-exposed monkey may have contributed to suprathreshold responses unrelated to Pb exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Exposed monkeys also expressed greater deterioration of auditory function compared to controls as they aged (Rice, 1998). Deficits in hearing at all frequencies on a pure tone detection task have been reported in adult monkeys developmentally exposed to lead (Laughlin, Luck, & Lasky, 2009). Studies of somatosensory functioning in monkeys have shown that animals exposed to methylmercury demonstrated elevated vibration detection thresholds, whereas results from lead-exposed monkeys were equivocal (Rice & Gilbert, 1995).…”
Section: Sensory Functioningmentioning
confidence: 99%